Synchronous primary diffuse large B-cell lymphoma and papillary thyroid carcinoma: a case report highlighting “Lymphoma first approach” - Rahim Dhanani; Ambreen Abdullah Unar; Muhammad Hassan Danish; Hamdan Ahmed Pasha; Ummiya Tahir; Mubasher Ikram (Journal of the Pakistan Medical Association, 2021)
Papillary thyroid carcinoma (PTC) is the most common type of all thyroid carcinomas and accounts for up to 90% of all thyroid malignancies. It is the most indolent form of the disease and has an excellent prognosis. On the other hand, Primary thyroid lymphoma (PTL) is a rare entity accounting for only about 1% to 5% of all thyroid malignancies and only 2% of extranodal lymphomas. Synchronous PTC and PTL is a very rare condition and only a few cases have been reported in the literature up till now. We report one such case in a 52-year-old lady who was referred to us with goiter and progressively increasing difficulty in breathing. Keywords: Synchronous thyroid malignancies, Papillary thyroid carcinoma, Lymphoma Continuous...